The Role of Employment Tests in Selecting Suitable Skills (A field study on administrators in the Government sector for the year 2024 AD) - Balkhair, Hanan Ali; Alshamasi, Areej Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to examine the role of employment tests, represented by their dimensions (personality test, knowledge test, and interest test), in selecting suitable skills in the government sector. It also sought to evaluate the extent of implementation of these tests and the degree to which they contribute to the selection of suitable skills. Furthermore, the study aimed to explore differences in the perspectives of the sample population regarding the relationship between the dimensions of employment tests and skill selection based on job-related variables. The study adopted the descriptive-analytical method and used a questionnaire as a data collection tool. The study population comprised all leaders and administrative staff in the government sector in the Makkah region, including presidents, deputies, directors, vice-directors, assistants, and administrative employees during the year 1446 AH/2024 CE. Due to the difficulty of identifying the total population, a convenience sampling method was employed, resulting in a sample of (235) participants. The study found that employment tests play a role in selecting suitable skills in the government sector. The overall level of employment tests implementation was very high, with an arithmetic mean of (4.35). The implementation levels for personality test, knowledge test and interest test were also very high, with arithmetic means of (4.34), (4.38) and (4.33), respectively. Additionally, the level of selecting suitable skills was very high, with an arithmetic mean of (3.56). No significant differences were found in the perspectives of the sample population regarding the relationship between the dimensions of employment tests and skill selection based on job-related variables such as (gender, age, educational qualification, years of experience, job title and government sector). The study recommended continuing the implementation of employment tests in government sectors and developing them according to a specific timeline based on the needs of each specialization within the sectors. It also suggested aligning the tests with the goals and aspirations of achieving the vision, utilizing performance measurement indicators to determine and select suitable skills and identifying minimum acceptable skill levels for employees using specific indicators.
Keywords: Employment Tests; Personality Test; Knowledge Test; Interest Test; Suitable Skills; Government Sectors